Development and characterization of layer-by-layer biosensors based on PEI(+)/GOx(-) layers using label-free methods - David, Melinda; Florescu, Monica; Barsan, Madalina M.; Tugulea, Laura; Brett, Christopher M. A. (Univerzita Pardubice, 2014)
Biosensors, as analytical devices, demonstrate unique efficiency in translating biochemical events into easily measurable electrical signals by using biological recognition elements, especially enzymes. Of the possible enzyme immobilisation methods, the layer-by-layer (LBL) technique, based on electrostatic interactions between layers, has the advantages of low cost, using small amount of materials, and leads to the formation of highly ordered and reproducible biosensor architectures. In this study, LbL biosensor construction has been evaluated. The substrates used were Au surfaces and mediated carbon-ink screen-printed electrodes. The gold electrodes were first functionalized with amino moieties by covalent linkage of cysteamine (Cys) through Au-S bonds. These allowed the linking of polyethyleneimine (PEI) through hydrogen-bonding to the gold surface and increased the stability of subsequent multilayers. PEI was directly adsorbed on the SPE surface. PEI is a short chain polymer and thence an efficient electron carrier, and being positively charged, it allows the formation of LBL structures with negatively charged enzymes. The multilayer formation of PEI(+)/GOx(-) was monitored by cyclic voltammetry, electrochemical impedance spectroscopy, and gravimetry. The influence of each enzymatic layer on the performance of the developed biosensor was analysed by fixed potential amperometric measurements.
Keywords: layer-by-layer biosensors; enzyme immobilization; voltammetric determination; electrochemical impedance spectroscopy; gravimetry; amperometric detection